Outcomes of patients who undergo percutaneous coronary intervention with covered stents for coronary perforation: A systematic review and pooled analysis of data. Issue 7 (18th December 2019) - Nagaraja, Vinayak; Schwarz, Konstantin; Moss, Stuart; Kwok, Chun Shing; Gunning, Mark
Abstract: Objectives: This review aims to evaluate the adverse outcomes for patients after treatment with covered stents. Background: Coronary perforation is a potentially fatal complication of percutaneous coronary revascularization which may be treated using covered stents. Studies have evaluated long‐term outcomes among patients who received these devices, but hitherto no literature review has taken place. Methods: We conducted a systematic review of adverse outcomes for patients after treatment with covered stents. Data from studies were pooled and outcomes were compared according to stent type. Results: A total of 29 studies were analyzed with data from 725 patients who received covered stents. The proportion of patients with chronic total occlusions, vein graft percutaneous coronary intervention (PCI), intracoronary imaging and rotational atherectomy were 16.9, 11.5, 9.2, and 6.6%, respectively. The stents used were primarily polytetrafluoroethylene (PTFE) (70%) and Papyrus (20.6%). Mortality, major adverse cardiovascular events, pericardiocentesis/tamponade and emergency surgery were 17.2, 35.3, 27.1, and 5.3%, respectively. Stratified analysis by use of PTFE, Papyrus and pericardial stents, suggested no difference in mortality ( p = .323), or target lesion revascularization ( p = .484). Stent thrombosis, pericardiocentesis/tamponade and emergency coronary artery bypass surgery (CABG) occurred more frequently in patients with PTFE stent use ( p = .011, p = .005, p = .012, respectively). In‐stent restenosis was more common with pericardial stent use (<.001, pooled analysis for first‐ and second‐generation pericardial stents). Conclusions: Cases of coronary perforation which require implantation of a covered stent are associated with a high rate of adverse outcomes. The use of PTFE covered stents appears to be associated with more stent thrombosis, pericardiocentesis/tamponade, and emergency CABG when compared to Papyrus or pericardial stents.